Implementasi nilai-nilai pancasila dalam masyarakat Indonesia - Vitaloka, Eka Dyah (Maliki Interdisciplinary Journal, 2025)
Pancasila serves as the establishment of the Indonesian state, enveloping five key standards that shape the system for administration and society. This article examines the usage of Pancasila values in lifestyle in Indonesia, counting advancing devout resistance, interest in races, the soul of shared participation, and women’s strengthening. Furthermore, the article investigates how instruction can serve as a medium for joining Pancasila values among the more youthful era. Through this approach, Pancasila remains important as a ethical and moral direct in building a fair and civilized society.